Selection Tests for Trainee Conference Interpreters - Gerver, David; Longley, Patricia; Long, John; Lambert, Sylvie (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1989)
AbstractThis preliminary study devised and tested a series of psychometric tests to facilitate selection of simultaneous and consecutive interpreter-trainee candidates. Twelve tests, based either on text materials, linguistic subskills or speed-stress, were correlated with judges' ratings of the final interpretation examination. Students who passed the exam had higher mean scores on all tests than those who failed. Test scores were positively inter-correlated between completion-detection tests and simultaneous interpretation ratings and between recall tests and consecutive examination ratings. Text-based tests were more predictive than subskills or speed-stress tests. The relationship between test type and interpreting is discussed together with possible reasons underlying differential performance on tests of the same kind.Problems in the recruitment and training of conference interpreters have been the frequent subject of debate by members of the profession (Keiser 1978; Longley 1978; Namy 1978). Although there have been some publications on psychological and other theoretical aspects of the interpreter's skills (Barik 1973; Gerver 1976; Seleskovitch 1976; Karmiloff-Smith 1978; Moser 1978; Chernov 1979; Lambert 1983), there has been no systematic research on student selection and training in this field.What qualities and skills are required for success as an interpreter or as a trainee in the field? Although no previous empirical research has been carried out on this subject, there does appear to be some consensus among interpreters and teachers of interpreting as to the skills and qualities sought in new members of the profession. A survey of articles written by members of the profession, as well as transcripts of interviews with working interpreters, suggested some agreement of the following as being essential for success as a trainee or in the profession.1. Profound knowledge of active and passive languages and cultures.2. Ability to grasp rapidly and convey the essential meaning of what is being said.3. Ability to project information with confidence, coupled with a good voice.4. Wide general knowledge and interests, and a willingness to acquire new information.5. Ability to work as a member of a team.The specific aim of the present study was to develop and evaluate objective tests to assess the second item mentioned above, that is the candidate's ability to grasp rapidly and to convey the meaning of spoken discourse. It was expected that the tests would contribute to improving selection procedures, hence the number of students passing the final examination, as well as the course itself.The present study arose from the decision of Patricia Longley, one of the co-authors and former director of the Interpretation Programme at the Polytechnic of Central London, to initiate the establishment of objective criteria for the selection of students for the postgraduate course in conference interpreting techniques at the School of Languages in London. The course, founded by Patricia Longley in 1963, and now headed by Jennifer MacKintosh, is an intensive six-month course in simultaneous and consecutive interpretation. Over 200 applications are received each year from candidates throughout the world, about half of whom are invited to London for interviews and informal tests, lasting a day. Only 25 to 30 candidates are selected for the course.The informal tests consist of written translation tests in addition to tests of both aural and oral language skills in the candidates' other languages. During the tests, candidates are first asked to repeat texts in the source language (shadowing) before progressing to interpretation of texts from their passive languages into their active language. These texts progress from simple sentences to more complex, albeit non-technical, longer passages. Unusual and unexpected phrases are inserted into the more difficult passages for interpretation in order to assess candidates' skills in coping with the unexpected and with passages which cannot be translated word-for-word. The interviews are designed to assess candidates' general background knowledge and interests, motivation, presentation of self, and general suitability for the profession. Whether or not there is a current market for the candidate's particular language combination is also taken into account at the time of selection.The intensive, six-month course involves training in both simultaneous and consecutive interpretation, and in the note-taking skills essential to the latter form of interpreting, in conference practices, and in a variety of subjects likely to be encountered in conference settings.The final examinations are oral in both forms of interpretation in the candidate's principal working languages, and are conducted by a board of external examiners who are themselves senior practising interpreters in major international organizations such as the U.N., Council of Europe, I.L.O., and the W.H.O.A secondary aim of the study was to explore alternative types of tests. Since the task of the interpreter is to transform spoken textual information from one language into another, either immediately (for simultaneous interpretation) or after some delay (for consecutive interpretation), the first type of test - termed text-based - assumed the processing of connected discourse to be a crucial feature of the interpreter's task. The approach was based on recent work in the area of text processing (Kintsch 1974; MacKintosh 1985). Text-based tests required either the recall of the information presented or the completion of individual target words in the text. The second type of test - termed subskill-based - assumed language subskills such as synonym generation, sentence re-expression and vocabulary selection to be an adequate reflection of the interpreter's task. The approach was based on the development of a set of factor referenced cognitive tests of verbal ability (Eckstrom et al. 1976). In addition, both simultaneous and consecutive interpretation are performed under conditions of speed-stress, since the interpreter is paced by the speaker over whom he has little or no control. Hence, the third type of test - termed stress-based-assumed speed stress to be a general performance factor not particular to, but exemplified by, interpreting. The approach was based on the development of a speed test requiring the solution of problems involving letter series performed under a time constraint (Furneaux 1956). It was expected that the present research would throw some light on whether text-based, subskill-based or speed stress-based tests reflected the crucial features of the interpreter's task for the purpose of testing trainee candidates' abilities.